Open spaces, nature-based solutions, and community appropriations - Barroso, Aline Maria Costa; Moura, Newton Célio Becker de (Technical and Scientific Journal Green Cities, 2025)
Objective – This article aims to describe two experiences of public university engagement, through extension projects, in the implementation and consolidation of open spaces, aiming at the appropriation of these places by surrounding communities. Methodology – The object of analysis in this article is public and open space, and the university’s engagement in these spaces spans a period of 10 years (2015 to 2025) in two different cities: Salvador and Fortaleza. Throughout this period, various actions were carried out involving different participatory methodologies for data collection, urban analysis, and collective construction aimed at implementing improvements in these areas. To enable publication, a temporal cut was made; therefore, only the activities carried out between 2023 and 2025 were detailed. Originality/relevance – The relevance of this article lies mainly in giving visibility to: the role of the public university, the community struggle for the implementation of quality open spaces, and the discussion on truly participatory methodologies that contribute to the improvement of these areas. Results – The main results achieved were: (i) in Salvador, the implementation of Saramandaia Square and the development of several ongoing actions to improve and foster community appropriation of this space, as well as the development of urban furniture studies to optimize these public areas; (ii) in Fortaleza, the university’s engagement with the local community, its training in nature-based solutions (NBS), and the future implementation of these solutions in the open space. Theoretical/methodological contributions – The main theoretical contributions relate to the discussion of participatory methodologies and community appropriation. Social and environmental contributions – The social and environmental contributions relate to the implementation of free, high-quality public spaces, as well as various awareness-raising actions and the inclusion of sustainable strategies in these places.